862Syncav with multipoint pacing improves acute left ventricular hemodynamics. (18th June 2020) - Chow, A; Waddingham, P; Betts, T; Mangual, J; Badie, N; Mcspadden, L; Pappone, C; Calo, L; Leyva, F; Thibault, B
Abstract: Funding Acknowledgements: Abbott Introduction: SyncAV has been shown to improve electrical synchronization by automatically adjusting atrioventricular delay (AVD) according to the intrinsic atrioventricular conduction time. Additional incremental electrical synchronization may be gained by the addition of second left ventricular (LV) pulse with MultiPoint Pacing (MPP). While the electrical synchronization benefits of SyncAV have been previously explored, there has been no assessment of the acute hemodynamic impact of SyncAV with or without MPP. Objective:  Evaluate the acute LV hemodynamic impact of SyncAV with and without MPP. Methods: Heart failure patients with LBBB and QRS duration (QRSd) > 140 ms undergoing CRT-P/D implant with a quadripolar LV lead were enrolled in this prospective study. A guidewire or catheter with pressure transducer was placed in the LV chamber and the maximum pressure change (dP/dtmax) was recorded during the following pacing modes:  intrinsic conduction, conventional biventricular pacing with SyncAV (BiV + SyncAV), and MPP with SyncAV (MPP + SyncAV). Twelve-lead surface ECG was used to determine the patient-tailored SyncAV offset that minimized QRSd. Results: Twenty-seven patients (67% male, 44% ischemic, 30 ± 7% ejection fraction) completed the acute recordings. Relative to the intrinsic QRSd of 163 ms, BiV + SyncAV reduced QRSd by 21.5% to 124 ms (p < 0.001 vs. intrinsic) and MPP + SyncAV reduced QRSd by 26.6% to 120 ms (p < 0.05 vs. BiV + SyncAV). Beyond electrical synchronization, SyncAV significantly improved acute hemodynamics. Relative to the intrinsic dP/dtmax of 842 mmHg/s, BiV + SyncAV elevated dP/dtmax by 6.3% to 900 mmHg/s (p < 0.001 vs. intrinsic) and MPP + SyncAV elevated dP/dtmax by 8.8% to 926 mmHg/s (p < 0.005 vs. BiV + SyncAV). Despite both QRSd and dP/dtmax improvement with SyncAV and MPP, correlation between electrical and hemodynamic measurements was poor (R2 = 0.0 for BiV + SyncAV, R2 = 0.1 for MPP + SyncAV). Conclusion: SyncAV may significantly improve acute LV hemodynamics in addition to electrical synchrony in LBBB patients. Further incremental improvement was achieved by combining SyncAV with MPP.